Leveraging Volunteerism and Digital Competencies to Overcome Innovation Barriers Among Nascent Entrepreneurs in Indonesia (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study explores how nascent entrepreneurs in Indonesia can improve their business innovation performance by utilizing volunteerism and digital competencies, particularly in the context of financial and technological limitations. These challenges significantly hinder their capacity for effective innovation, especially in resource-limited settings where access to tools and expertise is often scarce. A quantitative approach was employed, using data from 156 nascent entrepreneurs, which was analyzed through Structural Equation Modeling (SEM). The results indicate that the voluntary exchange of ideas and competences, framed through the Service-Dominant Logic (S-DL) perspective, plays a critical role in overcoming resource constraints and enhancing innovation outcomes. By facilitating collaboration and knowledge-sharing via volunteerism, nascent entrepreneurs can strengthen their digital and managerial capabilities, which are essential for driving innovation. The study highlights the importance of creating ecosystems that support stakeholder-driven volunteer initiatives, which help develop strategic digital competencies among emerging entrepreneurs, thereby fostering greater innovation capacity and ensuring long-term business sustainability.